2018
DOI: 10.1177/0190272518765134
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Social Schematic Model of Police Procedural Justice

Abstract: Procedural justice theory increasingly guides policing reforms in the United States and abroad. Yet the primary sources of perceived police procedural justice are still unclear. Building on social schema research, we posit civilians' perceptions of police procedural justice only partly reflect their personal and vicarious experiences with officers. We theorize perceptions of the police are anchored in a broader ''relational justice schema,'' composed of views about how respectful, fair, and unbiased most peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 132 publications
(204 reference statements)
2
62
0
Order By: Relevance
“…While this methodology has become common in the study of public attitudes towards the police (e.g. Gerber and Jackson, 2013 ; Tyler et al , 2014 ; Hamm et al , 2017 ; Pedersen et al , 2017 ; Pickett et al , 2018 ), it relies on nonprobability convenience samples. As noted earlier, the sample of this study closely resembles the population of adult, non-Orthodox Jews in Israel in terms of personal status, gender, age, and country of origin, but the observed difference in education may be partly attributed to the non-random sampling procedure.…”
Section: Discussionmentioning
confidence: 99%
“…While this methodology has become common in the study of public attitudes towards the police (e.g. Gerber and Jackson, 2013 ; Tyler et al , 2014 ; Hamm et al , 2017 ; Pedersen et al , 2017 ; Pickett et al , 2018 ), it relies on nonprobability convenience samples. As noted earlier, the sample of this study closely resembles the population of adult, non-Orthodox Jews in Israel in terms of personal status, gender, age, and country of origin, but the observed difference in education may be partly attributed to the non-random sampling procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that perceptions of the legitimacy of nonlegal authorities—such as one’s parents—are associated with rule violation in a similar way as police legitimacy evaluations (Cohn et al 2010, 2012; Trinkner and Cohn 2014). This line of research is part of a larger growing trend that has begun examining how social factors impact individuals’ attitudes toward criminal justice authority (Pickett, Nix, and Roche 2018). One promising line of research examines how parental assessments of legitimacy influence their children’s perceptions of the legitimacy of legal actors (Cavanagh and Cauffman 2015; Wolfe et al 2017).…”
Section: Age-graded Legitimacy Evaluation Developmentmentioning
confidence: 99%
“…The racial divide in fear may be mediated by past experiences with police mistreatment (16,17). Alternatively, it may reflect differences in other relevant experiences, in residential context, especially in perceived neighborhood conditions (17,18), in socioeconomic status, in family structure, or in political and religious socialization-factors that influence other types of fear and/or attitudes toward criminal justice. Our survey measured these potential sources of police-related fearfulness.…”
Section: Resultsmentioning
confidence: 99%